High-performance Thin-layer Chromatography Analysis for the Identification of Marker Compounds from Selected Medicinal Plants: Terminalia coriacea, Hydrolea zeylanica, Cytisus capitatus, and Dorycnium pentaphyllum - Patel, Jitendra (Asian Journal of Pharmaceutics (AJP), 2025)
The research sought to examine the marker chemicals in the extracts of four medicinal plants: Terminalia coriacea, Hydrolea zeylanica, Cytisus capitatus, and Dorycnium pentaphyllum utilizing high-performance thin-layer chromatography (HPTLC). The selection of these plants was based on their historical medicinal applications, with the study concentrating on identifying essential bioactive components, including flavonoids and tannins that enhance their therapeutic efficacy. Plant extracts were obtained by a solvent-based extraction process and thereafter analyzed with HPTLC under UV illumination at 254 nm and 366 nm for visualization. The research found Rutin as the marker compound for flavonoids and Gallic acid as the marker compound for tannins in plants. Rutin was identified in T. coriacea and C. capitatus, but Gallic acid was recognized in D. pentaphyllum and H. zeylanica. These compounds’ retention factor (Rf) values were documented and compared with reference standards for identification purposes. Moreover, a quantitative study of these marker compounds indicated that T. coriacea possesses the highest rutin content (3.2 mg/g), whereas D. pentaphyllum exhibits the highest gallic acid concentration (4.5 mg/g). The findings demonstrate that these plants include substantial concentrations of bioactive chemicals, warranting further investigation into their pharmacological potential. The research illustrates the efficacy of HPTLC as a method for the standardization, quality control, and verification of medicinal plants. It underscores the significance of chemical profiling in guaranteeing the therapeutic efficacy and safety of Phyto therapeutic agents.